Forest law No. 462 / Ariel Bucardo Rocha - Bucardo Rocha, Ariel (Nicaragua : MAGFOR, 2007)
General dispositions, of the nantional system of forestrey administration, organs and competencies, forestry mangement and usage, transportacion, storage and transformation, prevention, mitigation and plague control and forest fires, promotion and incentive for the forest development, forest consessions, payment for usage, dorest develpment fund, informations and sactions.
Index, map, table
Col. Agro
Keywords: 1. LAND REGULATION 2. FOREST LAW N° 462 3. PROPERTY 4. AGROFORESTRY